Challenges and Opportunities for the Development of Green Sukuk in Indonesia - Eka Septiana; Gemala Dewi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Indonesia's future economic development is directed at sustainable development that considers environmental aspects. This sustainable development requires funding support from both the government and the private sector. Sharia instruments in the capital market have the opportunity to be developed as sharia investment products that are environmentally sound, both green sukuk, blue sukuk, and green sharia mutual funds. Green sukuk are sukuk that are oriented towards development in land areas, while blue sukuk are focused on marine ecosystems. The diversification of thematic sukuk issuance can increase the choice of investors who have a preference for environmental concerns. On the other hand, there are still challenges from the issuance of these two types of instruments. These challenges include the identification of underlying assets that meet the sustainability requirements, the interest and readiness of the issuing company, as well as the limited number of parties conducting environmental assessments/certifications. In 2018, the Indonesian government issued a green sukuk which is the first green sukuk issued by a country in Asia. The issuance of the sovereign green sukuk was offered specifically for global investors and received appreciation from the international community. In 2019, the government again issued green sukuk intended for retail investors in Indonesia. The use of green sukuk that have been issued by the government is for the construction of new irrigation networks, drainage management in urban areas, as well as for the use of railway lines. After being initiated by the government with the issuance of green sukuk, it is expected that the development of environmentally friendly sukuk will be carried out by corporations, both green and blue sukuk. In addition, it is necessary to develop an environmentally friendly sharia index along with encouragement to investment managers to create sharia mutual fund products with environmental insight, such as green sharia mutual funds. OJK needs to work together with stakeholders in order to support the availability of adequate infrastructure to develop these environmentally sound investment products.